2022
DOI: 10.1017/s0007114522001416
|View full text |Cite
|
Sign up to set email alerts
|

Trends in dietary salt sources in Japanese adults: data from the 2007–2019 National Health and Nutrition Survey

Abstract: Identifying trends in dietary salt sources is essential for effectively reducing salt/sodium intake. This study aimed to examine the trends in dietary salt sources among Japanese adults using the 2007–2019 National Health and Nutrition Survey data collected from 95,581 adults aged ≥20 years. Dietary intake was estimated using the 1-day household-based dietary record. Foods reported as potential sources of salt intake in Japan and other countries were categorised into 21 groups. Salt intake for each food group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Regarding the association between age and salt intake, a previous study reported that ageing leads to a total reduction in dietary intake, and the consequence of such a reduction is a decrease in salt intake. 22 Although that study was conducted with mostly middle-aged and older adults, it may be fair to assume that a similar trend would be found among the haemodialysis patients in our study. Regarding salt reduction compliance, a previous study 23 reported that such compliance was associated with the perceived benefit of salt reduction for the future.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding the association between age and salt intake, a previous study reported that ageing leads to a total reduction in dietary intake, and the consequence of such a reduction is a decrease in salt intake. 22 Although that study was conducted with mostly middle-aged and older adults, it may be fair to assume that a similar trend would be found among the haemodialysis patients in our study. Regarding salt reduction compliance, a previous study 23 reported that such compliance was associated with the perceived benefit of salt reduction for the future.…”
Section: Discussionsupporting
confidence: 73%
“…In the future, it will be necessary to verify whether the 11 questionnaires identified in the present study can be used in the NHNS participants or sub-sample of them (not only in terms of validity and feasibility but also in terms of participation rates, and consistency with previous NHNS results). Additionally, although 11 questionnaires were extracted in the present study, the dietary patterns, energy, macro nutrient and salt intake among Japanese have changed over time ( 82 84 ) . It will be necessary to periodically examine the feasibility of using the questionnaires to monitor changes in the dietary intake of the Japanese population through the NHNS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in sodium intake to the shared meal frequency were observed between men and women. In men, although condiments (the largest food source for sodium intake) [ 41 ] increased with a shared meal frequency, sodium intake did not. One interpretation would be that the same condiment was consumed across the shared meal frequencies, and sodium intake from other food sources decreased in men; this is possible given that the intake of cereals (including bread and instant noodles) and confectioneries (including savory snacks) was reduced across the shared meal frequencies.…”
Section: Discussionmentioning
confidence: 99%